The Federal Republic of Germany’s attitude to the Eastern Partnership member states in the context of Germany’s eastern policy in the 21st century: implications for Poland (Economic and Political Thought, 2017)
The article presents the relations between the Federal Republic ofGermany and six member states of the Eastern Partnership programme,i.e. Ukraine, Belarus, Armenia, Azerbaijan and Georgia. The analysis alsocovers the attitude of the German federal government towards the EasternPartnership project as such, which was a Polish initiative supported by Sweden.The article also takes into consideration the implications of the Germaneastern policy carried out in the region for Poland.